AB0208 Reduced Hand Function Indicates Higher Disease Activity In Patients With Rheumatoid And Psoriatic Arthritis - Coppers, Birte; Heinrich, Simon; Bayat, Sara; Tascilar, Koray; Kleyer, Arnd; Simon, David; Minopoulou, Ioanna; Corte, Giulia; Fagni, Filippo; Schönau, Verena; Bohr, Daniela; Leyendecker, Sigrid; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Measuring disease activity in patients with inflammatory arthritis remains challenging and is mainly based on physician-dependent assessments, subjective measures and just one blood biomarker of inflammation with no indication of the subclinical or functional state of the patients [1, 2]. Patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) present with impaired hand function compared to healthy controls [3, 4]. While hand function is well studied in RA patients [5], data is sparse for PsA patients. Objectives: To employ the association between clinical disease activity scores and objectively measured hand function impairment in RA and PsA patients. Methods: Three conventional hand function tests were performed by PsA (CASPAR criteria) and RA (ACR/EULAR 2010 criteria) patients (Internal Medicine 3 outpatient clinics Erlangen, Germany) and healthy controls (HC) (study: Ethics #357_20B, DRKS00032490). The clinically assessed disease activity scores (Disease Activity in Psoriatic Arthritis Score (DAPSA) [1], Disease Activity Score 28 (DAS28) [2]) and the best trial for each of the hand function tests were used for this analysis: the highest out of three trials for an isometric grip strength test (Dynamometer, Saehan, Korea, Figure 1 A), the highest out of two trials for a dynamic grip strength test (Martin Vigorimeter, Germany, Figure 1 B) and the fastest out of two trials for the fine motor skill Moberg Picking-Up Test (MPUT) (Figure 1 C) for each hand. Mixed-effect linear regression models adjusted for age were used to employ the associations between the clinical disease activity scores and hand function tests of the patients. Analyses were stratified by sex. Results: We included 76 PsA patients (37 male, 52.0±4.3 years; DAPSA: 10.2±7.1), 73 RA patients (24 male, 53.9±14.1 years; DAS28: 2.6±0.9), and 77 HC (37 male, 46.0±18.5 years) in this study. For RA patients one-unit increase of the DAS28 was significantly associated with reduced dynamic grip strength for both sexes (Table 1, p<0.05) but not with a reduced isometric grip strength. Performance time of the MPUT was on average 11% (male) and 7% (female) longer with one-unit increase in the DAS28 score, but was not statistically significant. In PsA patients, a one-unit increase in the DAPSA score was associated with worse hand function on all measurements, but these were significant only in male patients (all p<0.05, Table 1). The MPUT showed worse performance of 2% in males and 1% in females for each one-point increase of the DAPSA score. Conclusion: Increased disease activity is associated with reduced hand function in PsA and RA patients. The dynamic grip strength test (vigorimeter) seems to be more sensitive than the isometric grip strength test (dynamometer) to detect functional changes in relation to disease activity. For male PsA patients, the fine motor MPUT may be particularly suitable to reflect changes in disease activity. Longitudinal properties of these measurements, such as sensitivity to change, need to be further explored. An overall low disease activity in PsA and RA patients is a limitation of our stud

AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Elie-Tino, Godonou; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

ABATACEPT DELAYS THE DEVELOPMENT OF RA-CLINICAL RESULTS AFTER 18 MONTHS FROM THE RANDOMIZED, PLACEBO-CONTROLLED ARIAA STUDY IN RA-AT RISK PATIENTS - Rech, Jürgen; Kleyer, Arnd; Ostergaard, M.; Hagen, Melanie; Valor, L.; Tascilar, Koray; Krönke, Gerhard; Schönau, Verena; Kleinert, Stefan; Baraliakos, X.; Braun, J.; Fleck, M.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Abatacept inhibits inflammation and onset of rheumatoid arthritis in individuals at high risk (ARIAA): a randomised, international, multicentre, double-blind, placebo-controlled trial - Rech, Jürgen; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Manger, Bernhard; Schönau, Verena; Hueber, Axel; Kleinert, Stefan; Baraliakos, Xenofon; Braun, Jürgen; Kiltz, Uta; Fleck, Martin; et al. (Lancet, 2024)
Background: Individuals with anti-citrullinated protein antibodies (ACPAs) and subclinical inflammatory changes in joints are at high risk of developing rheumatoid arthritis. Treatment strategies to intercept this pre-stage clinical disease remain to be developed. We aimed to assess whether 6-month treatment with abatacept improves inflammation in preclinical rheumatoid arthritis. Methods: The abatacept reversing subclinical inflammation as measured by MRI in ACPA positive arthralgia (ARIAA) study is a randomised, international, multicentre, double-blind, placebo-controlled trial done in 14 hospitals and community centres across Europe (11 in Germany, two in Spain, and one in the Czech Republic). Adults (aged ≥18 years) with ACPA positivity, joint pain (but no swelling), and signs of osteitis, synovitis, or tenosynovitis in hand MRI were randomly assigned (1:1) to weekly subcutaneous abatacept 125 mg or placebo for 6 months followed by a double-blind, drug-free, observation phase for 12 months. The primary outcome was the proportion of participants with any reduction in inflammatory MRI lesions at 6 months. The primary efficacy analysis was done in the modified intention-to-treat population, which included participants who were randomly assigned and received study medication. Safety analyses were conducted in participants who received the study medication and had at least one post-baseline observation. The study was registered with the EUDRA-CT (2014–000555–93). Findings: Between Nov 6, 2014, and June 15, 2021, 139 participants were screened. Of 100 participants, 50 were randomly assigned to abatacept 125 mg and 50 to placebo. Two participants (one from each group) were excluded due to administration failure or refusing treatment; thus, 98 were included in the modified intention-to-treat population. 70 (71%) of 98 participants were female and 28 (29%) of 98 were male. At 6 months, 28 (57%) of 49 participants in the abatacept group and 15 (31%) of 49 participants in the placebo group showed improvement in MRI subclinical inflammation (absolute difference 26·5%, 95% CI 5·9–45·6; p=0·014). Four (8%) of 49 participants in the abatacept group and 17 (35%) of 49 participants in the placebo group developed rheumatoid arthritis (hazard ratio [HR] 0·14 [0·04–0·47]; p=0·0016). Improvement of MRI inflammation (25 [51%] of 49 participants in the abatacept group, 12 [24%] of 49 in the placebo group; p=0·012) and progression to rheumatoid arthritis (17 [35%] of 49, 28 [57%] of 49; HR 0·14 [0·04–0·47]; p=0·018) remained significantly different between the two groups after 18 months, 12 months after the end of the intervention. There were 12 serious adverse events in 11 participants (four [8%] of 48 in the abatacept group and 7 [14%] of 49 in the placebo group). No deaths occurred during the study. Interpretation: 6-month treatment with abatacept decreases MRI inflammation, clinical symptoms, and risk of rheumatoid arthritis development in participants at high risk. The effects of the intervention persist through a 1-year drug-free observation phase. Funding: Innovative Medicine Initiative.
CRIS-Team Scopus Importer:2024-02-23

Abatacept Reverses Subclinical Arthritis in Patients with High-risk to Develop Rheumatoid Arthritis -results from the Randomized, Placebo-controlled ARIAA Study in RA-at Risk Patients - Rech, Jürgen; Hueber, Axel; Ostergaard, Mikkel; Tascilar, Koray; Hagen, Melanie; Mendez, Larissa Valor; Kleyer, Arnd; Krönke, Gerhard; Simon, David; Schönau, Verena; Hueber, Axel; Kleinert, Stefan; et al. (ARTHRITIS & RHEUMATOLOGY, 2021)
CRIS-Team WoS Importer:2022-03-11

Abatacept Significantly Reduces Subclinical Inflammation During Treatment (6 Months), This Persists After Discontinuation (12 Months), Resulting in a Delay in the Clinical Development of RA in Patients at Risk of RA (The ARIAA Study) - Rech, Jürgen; Kleyer, Arnd; Ostergaard, Mikkel; Hagen, Melanie; Mendez, Larissa Valor; Tascilar, Koray; Krönke, Gerhard; Schönau, Verena; Simon, David; Kleinert, Stefan; Baraliakos, Xenofon; Braun, Juergen; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Anatomical pattern of entheseal and synovial fibroblast activation in patients with psoriasis and its risk of developing psoriatic arthritis - Corte, Giulia; Atzinger, Armin; Temiz, Selahattin Alp; Noversa de Sousa, Rita; Mutlu, Melek Yalcin; Schönau, Verena; Raimondo, Maria Gabriella; Kleyer, Arnd; Kuwert, Torsten; Ramming, Andreas; Simon, David; Sticherling, Michael; et al. (RMD Open, 2024)
OBJECTIVES: To assess the presence and anatomical distribution of activated fibroblasts in the joints and entheses of patients with psoriasis with arthralgia and to test how fibroblast activation visualised by 68gallium-labelled fibroblast activation protein inhibitor-04 (68Ga-FAPI-04)-positron emission tomography (PET)/CT correlates with clinical tenderness, musculoskeletal ultrasound findings and progression to psoriatic arthritis (PsA). METHODS: We conducted a prospective cohort study in patients with psoriasis and arthralgia who underwent clinical and ultrasound evaluation and whole-body PET/CT imaging with 68Ga-FAPI-04. 68Ga-FAPI-04 uptake at synovial and entheseal sites was assessed by maximal standardised uptake values (SUVmax) and PET/CT Joint Index (JI); logistic regression models were used to investigate its correlation with clinical and ultrasound findings. Survival analyses were performed on patients with at least 6 months of follow-up. RESULTS: 36 patients with psoriasis were enrolled. 68Ga-FAPI-04 uptake was found in 318 (7.9%) joints and 369 (7.3%) entheses in 29 (80.6%) participants, with a mean SUVmax (SD) of 3.2 (1.8) for joints and 2.9 (1.6) for entheses. Large joints and the lower limbs were predominantly affected. A significant positive relationship was found between 68Ga-FAPI-04-PET/CT signal intensity and the 68 tender joint count (SUVmax: p<0.001; PET/CT-JI: p<0.001) and tender entheses count (SUVmax: p<0.001; PET/CT-JI: p=0.002). No correlations were found with ultrasound findings (SUVmax: p=0.969; PET/CT-JI: p=0.720). Patients with relevant synovio-entheseal 68Ga-FAPI-04 uptake showed a statistically significant higher risk of developing PsA (p=0.02), independent of ultrasound findings. CONCLUSIONS: Patients with psoriasis presenting with arthralgia show localised signs of resident tissue activation in joints and entheses, which are associated with higher risk of developing PsA.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Fibroblasts; Outcome Assessment; Health Care; Psoriatic Arthritis; Risk Factors; Ultrasonography

Blood-Based Biomarkers of Inflammation and Tissue Remodeling Can Discriminate Between Rheumatoid Arthritis, Psoriasis, and Psoriatic Arthritis and Are Associated with Hand Function - Port Linares, Helena; Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne-Christine; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Heinrich, Simon; et al. (poster, American College of Rheumatology Convergence, 2023)

CHARACTERIZATION OF RELAPSES IN PATIENTS WITH GIANT CELL ARTERITIS (GCA) PATIENTS- DATA FROM THE REAL-LIFE TREATMENT AND SAFETY (REATS)-GCA COHORT - Schönau, Verena; Corte, Giulia; Ott, Sabine; Tascilar, Koray; Hartmann, F.; Manger, Bernhard; Hellmich, B.; Pfeil, A.; Oelzner, P.; Schmidt, W. A.; Krause, A.; Schmalzing, M.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

CHRONIC TENOSYNOVITIS IS ASSOCIATED WITH LOSS OF GRIP STRENGTH IN PATIENTS WITH PSORIASIS AND PSORIATIC ARTHRITIS (OP0069) - Bayat, Sara; Coppers, Birte; Kleyer, Arnd; Elie-Tino, Godonou; Valor, L.; Simon, David; Fagni, Filippo; Corte, Giulia; Schönau, Verena; Tascilar, Koray; Hueber, Axel; Sticherling, Michael; et al. (Annals of the Rheumatic Diseases, 2023)
Background Rheumatic diseases result in joint destruction and impaired physical function [1]. We recently showed, that hand function based on objective tests may serve as a biomarker representing subclinical inflammation in psoriasis (Pso) patients and thus could support the early detection of psoriatic arthritis (PsA) onset [2]. Hand function tests are relevant for objective assessment of musculoskeletal function in relation to disease activity in PsA [3], However, the relationship of hand function with the synovitis and tenosynovitis detected by ultrasound (US) in PsA and Pso patients has not been well studied. Objectives To investigate the association of synovitis and tenosynovitis detected by US in greyscale (GS) and power doppler (PD) activity with grip strength and fine motor skills in patients with PsA and Pso. Methods PsA and Pso patients were recruited from the Rheumatology Department at the University Hospital erlangen, for this cross-sectional study. After giving written informed consent, subject characteristics were recorded and study participants underwent bilateral US of the wrists, metacarpophalangeal (MCP) joints, and flexor tendons of all fingers. Each joint was examined by GS (0-3), PD (0-3) and finally a combined score (PDUS: PD + GS) was calculated (0-3) [4]. The flexor tendon was scanned in GS (0/1) and with PD [0-3]. US activity considered either a synovitis or tenosynovitis score ≥1. Activity in tender joint count (TJC) and swollen joint count (SJC) 68/66 was considered ≥1 tender or ≥1 swollen joint. Hand function was assessed by vigorimetric grip strength (lbf) and the fine motor skill MPUT (Moberg pick-up test). For the analysis, patients’ hands were either divided in dominant/non-dominant or patient reported affected/non-affected hand. A correlation matrix was applied to measure the linear relation between the pairs of synovitis and tenosynovitis scores, grip strength and MPUT for both hands, using the Spearman correlation method. Results 106 patients (40 PsA, 66 Pso) participated in this study. Subject characteristics and general outcomes are summarized in Table 1. While grip strength was higher in the dominant hand (p<0.001), MPUT times are comparable between the dominant vs. non-dominant hands (p=0.056) but was faster in the non-affected hand (p=0.008). Low to moderate positive correlations were observed between both, overall GS synovitis score (MCP 2-5 + wrist) (r=0.24, p<0.05), and PDUS (r=0.23, p<0.05) with MPUT. In US active patients, a high correlation between grip strength and GS tenosynovitis score in digit 2 (r=-0.566, p=0.028) was detected. When considering patients with US in addition to SJC/TJC activity, imaging modalities did not correlate with hand function. Conclusion These findings indicate that the synovitis detected by greyscale is related with fine motor skills and tenosynovitis in greyscale with grip strength. This suggests, that chronic tenosynovitis has a greater impact on hand function than the acute inflammatory phase. When considering patients with TJC68/SJC66 ≥1 this relation is not present, suggesting that clinically assessed joint count, unlike ultrasonography, does not correlate with hand function impairmen

Cinematic rendering in rheumatic diseases-Photorealistic depiction of pathologies improves disease understanding for patients - Pachowsky, Milena; Morf, Harriet; Simon, David; Schönau, Verena; Valor-Mendez, Larissa; Knitza, Johannes; Fagni, Filippo; Engel, Klaus; Uder, Michael; Hueber, Axel; Schmidkonz, Christian; Schett, Georg; et al. (Frontiers in Medicine, 2022)
BackgroundPatient education is crucial for successful chronic disease management. Current education material for rheumatic patients however rarely includes images of disease pathologies, limiting patients' disease understanding. Cinematic rendering (CR) is a new tool that allows segmentation of standard medical images (DICOMs) into pictures that illustrate disease pathologies in a photorealistic way. Thus CR has the potential to simplify and improve the explanation of disease pathologies, disease activity and disease consequences and could therefore be a valuable tool to effectively educate and inform patients about their rheumatic and musculoskeletal disease (RMD). ObjectivesTo examine the feasibility of creating photorealistic images using CR from RMD patients depicting typical rheumatic disease pathologies and, in a second step to investigate the patient-perceived educational potential of these photorealistic images in clinical routine. MethodsWe selected conventional, high-resolution (HR) and positron emission tomography (PET) computed tomography (CT) images of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), axial spondyloarthritis (axSpA), and giant cell arteritis (GCA) that showed typical respective disease pathologies. These images were segmented using CR technique. In a prospective study, physicians used CR-enhanced and conventional original images to explain the depicted pathognomonic pathologies to patients with the respective rheumatic disease. Patients were then asked to complete a questionnaire evaluating the perceived usefulness of being presented with CR-enhanced images to better understand their underlying disease. ResultsCR images were successfully generated from above mentioned CT methods. Pathologies such as bone erosions, bony spurs, bone loss, ankylosis, and PET-based inflammation could be visualized in photorealistic detail. A total of 79 patients (61% females) with rheumatic diseases (RA 29%, PsA 29%, axSpA 24%, GCA 18%) were interviewed and answered the quantitative questionnaire. Mean age was 55.4 +/- 12.6 years. Irrespective of disease, all patients agreed or highly agreed that CR-based images help to improve disease understanding, should be shown at disease onset, provide a rationale to regularly take medication and would like to have access to their own CR-enhanced images. ConclusionConventional disease images can successfully be turned into photorealistic disease depictions using CR. Patients perceived CR images as a valuable addition to current patient education, enabling personalized disease education and potentially increased medication adherence.
CRIS-Team WoS Importer:2022-08-26

Classification of rheumatoid arthritis from hand motion capture data using machine learning - Fleischmann, Sophie; Holzwarth Correa, Vivien; Coppers, Birte; Sadeghi, Misha; Richer, Robert; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Vossiek, Martin; Schönau, Verena; Schett, Georg; Koelewijn, Anne; et al. (13. Kongress der Deutschen Gesellschaft für Biomechanik (DGfB), 2024)
Intro Classifying movement restrictions in patients with rheumatoid arthritis (RA) is challenging. Machine learning (ML) can identify patterns in the data that cannot be captured with statistical tools. Aim To test the feasibility of classifying RA patients and controls from hand motion capture data using automatic feature extraction (AFE) and ML and to evaluate if a larger feature set improves the performance. Methods 24 RA patients (ACR/EULAR 2010 criteria) and 23 controls performed tipping and flexion of the hand [1], which was captured by an optoelectronic measurement system at 100 Hz with 29 reflective markers placed on the hand dorsum. We extracted the 3D trajectories, expressed relative to the central wrist marker and normalized to the hand length, of 24 markers on one hand (excluding thumb markers). After linearly interpolating missing values we filtered the data using a 4th-order Butterworth filter at a 6 Hz cut-off frequency and extracted a minimal and extensive feature set from the hand trajectories using the AFE package tsfresh [2]. We compared 4 classifiers in combination with scaling and dimensionality reduction (Fig 1). For every combination of algorithms, we trained a model using a stratified 10-fold nested cross-validation (CV). Hyperparameters were found from an inner five-fold CV on the respective train set using grid search. We report the accuracy of the best model averaged over the 10 folds. Results The best accuracy was 68.2% for flexion and 62.7% for tipping (Fig 2). Using the extensive instead of the minimal feature set led to no major change in accuracy. Summary The classification performance based on AFE was below the anticipated level of accuracy (>70%), likely due to the small dataset with limited data quality. We currently evaluate the approach on a more consistent, larger dataset and include expert features in addition to AFE. References [1] Phutane et al., Sensors, 21(4), 1208, 2021 [2] Christ et al., Neurocomputing, 307, 72-77, 20

Comparison of diagnostic spectrum between inflammation of unknown origin and fever of unknown origin: A systematic review and meta-analysis - Betrains, Albrecht; Moreel, Lien; Mulders-Manders, Catharina M.; Auwaerter, Paul G.; Torné-Cachot, Joaquim; Weitzer, Friedrich; Terasawa, Teruhiko; Ly, Kim H.; Schönau, Verena; Blockmans, Daniel; Wright, William F.; Rovers, Chantal; et al. (European Journal of Internal Medicine, 2024)
Background: Patients with inflammation of unknown origin (IUO) and fever of unknown origin (FUO) are commonly considered a single population. Differences in underlying causes between both groups may steer the diagnostic work-up. Methods: PubMed, Embase, Web of Science, and ClinicalTrials.gov were searched from July 2009 through December 2023. Studies including both FUO and IUO patients with a sample size of ≥20 were considered. The primary outcome was the difference in the rate of patients affected by predefined diagnostic categories according to meeting FUO or IUO criteria. Data were pooled using random-effects models. Results: A total of 8 studies met criteria for inclusion, with a total of 1452 patients (466 with IUO and 986 with FUO). The median rate of IUO patients among the included studies was 32 % (range 25–39 %). Patients with IUO had a lower likelihood of infection (OR 0.59 [95 % CI; 0.36–0.95]; I2 0 %). There were no significant differences in the rate of noninfectious inflammatory disorders, malignancies, miscellaneous disorders, or remaining undiagnosed. Comparison of diagnostic subgroups revealed that IUO patients were less likely to have systemic autoinflammatory disorders (OR 0.17 [95 % CI, 0.05–0.58]; I2 42 %) and more likely to have vasculitis (OR 2.04 [95 % CI, 1.23–3.38]; I2 21 %) and rheumatoid arthritis or spondylarthritis (OR 3.52 [95 % CI, 1.16–10.69]; I2 0 %). Conclusion: Based on our findings, there is little reason to assume that FUO and IUO patients would benefit from a different initial diagnostic approach.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Diagnostic categories; Diagnostic spectrum; FUO; IUO

Detection of pre-existing neutralizing antibodies against Ad26 in HIV-1-infected individuals not responding to the Ad26.COV2.S vaccine - Schmidt, Katja; Harrer, Ellen; Schönau, Verena; Simon, David; Kleyer, Arnd; Steininger, Philipp; Korn, Klaus; Schett, Georg; Knobloch, Carina; Nganou-Makamdop, Krystelle; Harrer, Thomas (Infection, 2023)
Purpose: The Ad26.COV2.S vaccine is a replication-incompetent human adenovirus type 26 vector encoding the SARS-CoV-2 spike protein. In a phase 1-2a trial, a single dose of Ad26.COV2.S induced SARS-CoV-2 spike-specific antibodies in ≥ 96% of healthy adults. To investigate vaccine immunogenicity in HIV-1-infection, we measured SARS-CoV-2 spike-specific antibodies in Ad26.COV2.S vaccinated HIV-1-infected patients and analyzed the presence of pre-existing Ad26 neutralizing antibodies. Methods: We included all Ad26.COV2.S vaccinated HIV-1-infected patients of Erlangen HIV cohort fulfilling all inclusion criteria. The study cohort consisted of 15 HIV-1-infected patients and three HIV-1-uninfected subjects who received the Ad26.COV2.S vaccine between April and November 2021. Pre-vaccination sera were collected between October 2014 and June 2021, post-vaccination sera between June and December 2021. Neutralizing antibodies towards Ad26 were determined by a FACS-based inhibition assay measuring the expression of SARS-CoV-2 spike and adenoviral proteins in HEK293T cells after in-vitro transduction with Ad26.COV2.S or the control ChAdOx1-S. Results: Six out of 15 HIV-1-infected patients failed to develop SARS-CoV-2-specific antibodies and four patients developed weak antibody responses after vaccination with Ad26.COV2.S. Pre-vaccination sera of four of the six vaccine non-responders showed neutralizing activity towards Ad26.COV2.S but not toward the ChAdOx1-S vaccine at 1:50 dilution. After Ad26.COV2.S vaccination, 17 of the 18 subjects developed strong Ad26-neutralizing activity and only one of the 18 subjects showed neutralizing activity towards the ChAdOx1-S vaccine. Conclusion: Ad26.COV2.S vaccination showed a high failure rate in HIV-1-infected patients. Pre-existing immunity against Ad26 could be an important contributor to poor vaccine efficacy in a subgroup of patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Ad26.COV2.S; Adenovirus 26; HIV-1; Neutralizing antibodies; SARS-CoV-2; SARS-CoV-2 vaccine

Does Subjectively Perceived Loss Of Hand Function Sufficiently Represent Ultrasonography-Detected Synovitis And Tenosynovitis In Patients With Psoriasis And Psoriatic Arthritis? - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Schönau, Verena; Sticherling, Michael; Schett, Georg; Kleyer, Arnd; et al. (poster, European Alliance of Association for Rheumatology (EULAR) Congress, 2023)

Efficacy and safety of SARS-CoV-2 revaccination in non-responders with immune-mediated inflammatory disease - Simon, David; Tascilar, Koray; Fagni, Filippo; Schmidt, Katja; Krönke, Gerhard; Kleyer, Arnd; Ramming, Andreas; Schönau, Verena; Bohr, Daniela; Knitza, Johannes; Harrer, Thomas; Manger, Karin; et al. (Annals of the Rheumatic Diseases, 2021)
Objectives To test whether patients with immune-mediated inflammatory disease (IMIDs), who did not respond to two doses of the SARS-CoV-2 vaccine, develop protective immunity, if a third vaccine dose is administered. Methods Patients with IMID who failed to seroconvert after two doses of SARS-CoV-2 vaccine were subjected to a third vaccination with either mRNA or vector-based vaccines. Anti-SARS-CoV-2 IgG, neutralising activity and T cell responses were assessed at baseline and 3 weeks after revaccination and also evaluated seprarately in rituximab (RTX) and non-RTX exposed patients. Results 66 non-responders were recruited, 33 treated with RTX, and 33 non-exposed to RTX. Overall, 49.2% patients seroconverted and 50.0% developed neutralising antibody activity. Seroconversion (78.8% vs 18.2%) and neutralising activity (80.0% vs 21.9%) was higher in non-RTX than RTX-treated patients with IMID, respectively. Humoral vaccination responses were not different among patients showing positive (59.3%) or negative (49.7%) T cell responses at baseline. Patients remaining on mRNA-based vaccines showed similar vaccination responses compared with those switching to vector-based vaccines. Conclusions Overall, these data strongly argue in favor of a third vaccination in patients with IMID lacking response to standard vaccination irrespective of their B cell status.
CRIS-Team WoS Importer:2021-12-03

Establishment and evaluation of a sensor-based method to assess hand function in patients with rheumatoid arthritis - Coppers, Birte; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Heinrich, Simon; Bayat, Sara; et al. (conference, World Biomechanics Congress 2022, 2022)

Evaluation of marker-based motion capturing to charactherize basic hand movements in rheumatic patients - Coppers, Birte; Heinrich, Simon; Phutane, Uday; Berisha, Dardan; Tascilar, Koray; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; et al. (27th Congress of the European Society of Biomechanics, 2022)

Impact of Cytokine Inhibitor Therapy on the Prevalence, Seroconversion Rate, and Longevity of the Humoral Immune Response Against SARS-CoV-2 in an Unvaccinated Cohort - Simon, David; Tascilar, Koray; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, Johanna; Liphardt, Anna-Maria; Schönau, Verena; et al. (Arthritis and Rheumatology, 2022)
Objective To investigate the impact of biologic disease-modifying antirheumatic drug (bDMARD) treatment on the prevalence, seroconversion rate, and longevity of the humoral immune response against SARS-CoV-2 in patients with immune-mediated inflammatory diseases (IMIDs). Methods Anti-SARS-CoV-2 IgG antibodies were measured in a prospective cohort of health care professional controls and non-health care controls and IMID patients receiving no treatment or receiving treatment with conventional or biologic DMARDs during the first and second COVID-19 waves. Regression models adjusting for age, sex, sampling time, and exposure risk behavior were used to calculate relative risks (RRs) of seropositivity. Seroconversion rates were assessed in participants with polymerase chain reaction (PCR)-positive SARS-CoV-2 infection. Antibody response longevity was evaluated by reassessing participants who tested positive during the first wave. Results In this study, 4,508 participants (2,869 IMID patients and 1,639 controls) were analyzed. The unadjusted RR (0.44 [95% confidence interval (95% CI) 0.31-0.62]) and adjusted RR (0.50 [95% CI 0.34-0.73]) for SARS-CoV-2 IgG antibodies were significantly lower in IMID patients treated with bDMARDs compared to non-health care controls (P < 0.001), primarily driven by treatment with tumor necrosis factor inhibitors, interleukin-17 (IL-17) inhibitors, and IL-23 inhibitors. Adjusted RRs for untreated IMID patients (1.12 [95% CI 0.75-1.67]) and IMID patients receiving conventional synthetic DMARDs (0.70 [95% CI 0.45-1.08]) were not significantly different from non-health care controls. Lack of seroconversion in PCR-positive participants was more common among bDMARD-treated patients (38.7%) than in non-health care controls (16%). Overall, 44% of positive participants lost SARS-CoV-2 antibodies by follow-up, with higher rates in IMID patients treated with bDMARDs (RR 2.86 [95% CI 1.43-5.74]). Conclusion IMID patients treated with bDMARDs have a lower prevalence of SARS-CoV-2 antibodies, seroconvert less frequently after SARS-CoV-2 infection, and may exhibit a reduced longevity of their humoral immune response.
CRIS-Team WoS Importer:2022-04-08

LONG-TERM HUMORAL RESPONSE TO SARS-COV-2 VACCINATION IN PATIENTS WITH IMMUNE-MEDIATED INFLAMMATORY DISEASE - Tascilar, Koray; Simon, David; Kleyer, Arnd; Fagni, Filippo; Krönke, Gerhard; Meder, Christine; Dietrich, Peter; Orlemann, Till; Kliem, Thorsten; Moessner, J.; Liphardt, Anna-Maria; Schönau, Verena; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Objective and subjective hand function reflect grade of tenosynovitis in patients with psoriasis and psoriatic arthritis - Coppers, Birte; Bayat, Sara; Elie-Tino, Godonou; Valor-Mendez, Larissa; Simon, David; Corte, Giulia; Tascilar, Koray; Hueber, Axel; Bohr, Daniela; Schönau, Verena; Sticherling, Michael; Schett, Georg; et al. (poster, Deutsche Gesellschaft für Rheumatologie Kongress, 2023)

PHOTOREALISTIC DEPICTION OF RHEUMATIC PATHOLOGIES BY CINEMATIC RENDERING FACILITATES DISEASE UNDERSTANDING OF PATIENTS WITH RHEUMATIC DISEASES - Pachowsky, Milena; Morf, Harriet; Simon, David; Schönau, Verena; Valor, L.; Knitza, Johannes; Engel, K.; Uder, Michael; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen

Risk loci involved in giant cell arteritis susceptibility: a genome-wide association study - Borrego-Yaniz, Gonzalo; Ortiz-Fernández, Lourdes; Madrid-Paredes, Adela; Kerick, Martin; Hernández-Rodríguez, José; Mackie, Sarah L.; Vaglio, Augusto; Castañeda, Santos; Solans, Roser; Mestre-Torres, Jaume; Khalidi, Nader; Langford, Carol A.; et al. (The Lancet Rheumatology, 2024)
Background: Giant cell arteritis is an age-related vasculitis that mainly affects the aorta and its branches in individuals aged 50 years and older. Current options for diagnosis and treatment are scarce, highlighting the need to better understand its underlying pathogenesis. Genome-wide association studies (GWAS) have emerged as a powerful tool for unravelling the pathogenic mechanisms involved in complex diseases. We aimed to characterise the genetic basis of giant cell arteritis by performing the largest GWAS of this vasculitis to date and to assess the functional consequences and clinical implications of identified risk loci. Methods: We collected and meta-analysed genomic data from patients with giant cell arteritis and healthy controls of European ancestry from ten cohorts across Europe and North America. Eligible patients required confirmation of giant cell arteritis diagnosis by positive temporal artery biopsy, positive temporal artery doppler ultrasonography, or imaging techniques confirming large-vessel vasculitis. We assessed the functional consequences of loci associated with giant cell arteritis using cell enrichment analysis, fine-mapping, and causal gene prioritisation. We also performed a drug repurposing analysis and developed a polygenic risk score to explore the clinical implications of our findings. Findings: We included a total of 3498 patients with giant cell arteritis and 15 550 controls. We identified three novel loci associated with risk of giant cell arteritis. Two loci, MFGE8 (rs8029053; p=4·96 × 10–8; OR 1·19 [95% CI 1·12–1·26]) and VTN (rs704; p=2·75 × 10–9; OR 0·84 [0·79–0·89]), were related to angiogenesis pathways and the third locus, CCDC25 (rs11782624; p=1·28 × 10–8; OR 1·18 [1·12–1·25]), was related to neutrophil extracellular traps (NETs). We also found an association between this vasculitis and HLA region and PLG. Variants associated with giant cell arteritis seemed to fulfil a specific regulatory role in crucial immune cell types. Furthermore, we identified several drugs that could represent promising candidates for treatment of this disease. The polygenic risk score model was able to identify individuals at increased risk of developing giant cell arteritis (90th percentile OR 2·87 [95% CI 2·15–3·82]; p=1·73 × 10–13). Interpretation: We have found several additional loci associated with giant cell arteritis, highlighting the crucial role of angiogenesis in disease susceptibility. Our study represents a step forward in the translation of genomic findings to clinical practice in giant cell arteritis, proposing new treatments and a method to measure genetic predisposition to this vasculitis. Funding: Institute of Health Carlos III, Spanish Ministry of Science and Innovation, UK Medical Research Council, and National Institute for Health and Care Research
CRIS-Team Scopus Importer:2024-05-31

Sensor-assessed grasping time as a biomarker of functional impairment in rheumatoid arthritis - Coppers, Birte; Heinrich, Simon; Tascilar, Koray; Phutane, Uday; Kleyer, Arnd; Simon, David; Bräunig, Johanna; Penner, Johann; Vossiek, Martin; Schönau, Verena; Bayat, Sara; Schett, Georg; et al. (Scientific Reports, 2025)
Quantifying physical impairment in rheumatoid arthritis (RA) is important to determine disease burden and disability. Therefore, we aimed to define hand function impairments in RA patients using an opto-electronic measurement system (OMS). In this cross-sectional pilot study, spatio-temporal and hand segment data were collected during the fine motor skill Moberg Picking-Up Test (MPUT) and two elementary hand movement tasks in RA patients and healthy controls (HC) using a marker-based OMS. The duration of two MPUT movement phases (grasping, transporting 12 objects) and kinematic characteristics during the elementary movements were evaluated. We analyzed between-group differences using linear mixed-effects models accounting for within-participant clustering of hands and adjusting for age and sex. Measurements were obtained from 24 RA and 23 HC. The mean duration of the grasping phase of MPUT was longer in RA patients compared to HC while transporting times were identical, showing a significant group-phase interaction (p < 0.001). Interphalangeal joint angle ratios were similar in RA and HC (p > 0.05) with a lower ratio in both groups for the task thumb-finger opposition compared to flexion of joints. In RA patients especially grasping objects was impaired, and performance time for a subset of objects may serve as a quantitative biomarker of functional impairment.<br
CRIS-Team Scopus Importer:2025-03-14
Keywords: Biomarkers; Biomechanics; Fine-motor skills; Hand; Rheumatoid arthritis

Serum extracellular matrix biomarkers in rheumatoid arthritis, psoriatic arthritis and psoriasis and their association with hand function - Port, Helena; Coppers, Birte; Tragl, Sonja; Manger, Eva; Niemiec, Lisa Maria; Bayat, Sara; Simon, David; Fagni, Filippo; Corte, Giulia; Bay-Jensen, Anne Christine; Tascilar, Koray; Hueber, Axel; et al. (Scientific Reports, 2025)
Inflammatory arthritis, including rheumatoid arthritis and psoriatic arthritis, is characterized by physical function impairment. This becomes apparent even before arthritis onset, as in psoriasis (PsO). Chronic inflammation triggers an accelerated remodeling of the extracellular matrix (ECM), resulting in released ECM fragments detectable in blood. We aimed to investigate levels of blood-based ECM biomarkers in patients with RA, PsA, PsO, and healthy controls and to explore the association of ECM biomarkers with hand function impairments. Patients with RA (n = 85), PsA (n = 115), PsO (n = 102) and controls (n = 110) were included in this cross-sectional study. ECM catabolic (C1M, C2M, C3M, C4M, PRO-C4, C6M, ARG), formation (PRO-C1, PRO-C3, PRO-C6) and inflammation biomarkers (VICM) were measured in serum from all patients. Objective hand function (fine motor skills (Moberg-Picking-Up Test), isometric grip strength (dynamometer) and patient-perceived hand function (Michigan Hand Questionnaire (MHQ)) were assessed. Patients with RA and PsA received treatment with disease-modifying anti-rheumatic drugs. VICM levels were higher in RA, PsA, and PsO than in controls (p < 0.0001). PsA and PsO showed higher C4M levels compared to controls (p < 0.0001, p < 0.0001), while C6M was lower in patients with RA, PsA and PsO than in controls (p < 0.0001, p < 0.001, p < 0.01). PsO presented with higher levels of C1M compared to controls and to RA (p < 0.001 and p < 0.0001). PRO-C6 correlated negatively with MHQ (ρ = -0.39, p < 0.01) and grip strength (ρ = -0.31, p < 0.05) in PsO, while only weak correlations were observed between biomarkers and hand function scores for RA and PsA patients (all ρ < ± 0.2–0.3). Patients with RA, PsA, and PsO showed significant alterations in ECM remodeling biomarkers. Especially PsA and PsO had higher levels of inflammatory biomarkers compared to RA and controls, likely due to modulation by treatment. Predominantly in PsO, ECM formation biomarkers were associated with hand function impairments.<br
Keywords: Extracellular matrix; Biochemical markers; Rheumatoid arthritis; Psoriatic arthritis; Psoriasis; Hand function